2020
DOI: 10.1002/humu.23993
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the first missense variant in CEP78 , a founder allele associated with cone‐rod dystrophy, hearing loss, and reduced male fertility

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractInactivating variants in the centrosomal CEP78 gene have been found in cone-rod dystrophy with hearing loss (CRDHL), a particular phenotype distinct from Usher syndrome. Here, we identified and functionally characterized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 57 publications
6
47
0
Order By: Relevance
“…The latter result is in line with previous reports showing that the LRR region in the N-terminus of CEP78, which encompasses residue L150, is important for its localization to centrioles [27,35]. Both FLAG fusions were expressed at similar levels in the cells (Figure 2-figure supplement 1A, B); this was somewhat surprising given that endogenous CEP78 L150S is largely undetectable by western blot analysis of patient-derived HSFs suggesting its stability is compromised [30]. Therefore, we tested if the L150S mutation might affect binding of the CEP78 antibody used in [30] to CEP78.…”
Section: Analysis Of Rpe1 Wt and Cep78 Ko Cells Expressing Flag-cep78supporting
confidence: 91%
See 2 more Smart Citations
“…The latter result is in line with previous reports showing that the LRR region in the N-terminus of CEP78, which encompasses residue L150, is important for its localization to centrioles [27,35]. Both FLAG fusions were expressed at similar levels in the cells (Figure 2-figure supplement 1A, B); this was somewhat surprising given that endogenous CEP78 L150S is largely undetectable by western blot analysis of patient-derived HSFs suggesting its stability is compromised [30]. Therefore, we tested if the L150S mutation might affect binding of the CEP78 antibody used in [30] to CEP78.…”
Section: Analysis Of Rpe1 Wt and Cep78 Ko Cells Expressing Flag-cep78supporting
confidence: 91%
“…Several studies have shown that loss-of-function mutations in CEP78 are causative of ciliopathy characterized by CRDHL [29][30][31][32], and that cells lacking CEP78 display reduced ciliation frequency [34] or abnormally long cilia [29,30]. However, the molecular mechanisms by which CEP78 regulates cilium biogenesis and length were so far unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from CRDHL, sperm abnormalities causing infertility have been reported in two unrelated affected males (Ascari et al, 2020). Functional studies pointed to a lossof-function effect with decreased amounts of protein, normal subcellular localization, and elongated primary cilia in patients' cells (Namburi et al, 2016;Nikopoulos et al, 2016;Ascari et al, 2020). Interestingly, a complex SV implicating CEP78 has been reported in one individual with CRDHL, being a homozygous deletion-inversion-deletion overlapping CEP78 (Sanchis-Juan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the more recently identified disease genes that contribute to the genetic heterogeneity of IRD is the centrosomal gene CEP78 (MIM# 617110), in which several types of variants, inactivating sequence variants as well as a unique missense variant have been found in autosomal recessive conerod dystrophy with hearing loss (CRDHL; MIM# 617236), a recognizable phenotype distinct from Usher syndrome (Fu et al, 2016;Namburi et al, 2016;Nikopoulos et al, 2016;Ascari et al, 2020). Apart from CRDHL, sperm abnormalities causing infertility have been reported in two unrelated affected males (Ascari et al, 2020). Functional studies pointed to a lossof-function effect with decreased amounts of protein, normal subcellular localization, and elongated primary cilia in patients' cells (Namburi et al, 2016;Nikopoulos et al, 2016;Ascari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%